2014
DOI: 10.3390/molecules19044560
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of the Chemical Composition and Antimicrobial and Cytotoxic Activities of the Essential Oils from Inga laurina (Sw.) Willd.

Abstract: Abstract:The seasonal chemical composition of essential oils from Inga laurina was determined by GC/MS. In the stem bark's essential oil extracted during the dry season, the presence of terpenoids (30.05%) stood out, and phytol (9.76%) was the major compound identified. For the stem bark oil obtained during the rainy season, in addition to terpenoids (26.63%), a large amount of fatty acids (46.84%) were identified, in particular palmitic acid (25.40%). Regarding the leaves' essential oil obtained in the dry se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 44 publications
1
9
0
4
Order By: Relevance
“…24 Several fatty acids have been studied alone or in mixtures, and have shown antimicrobial and antifungal activities against different microorganisms. 25,26,27 Furthermore, these fatty acids have high commercial value.…”
mentioning
confidence: 99%
“…24 Several fatty acids have been studied alone or in mixtures, and have shown antimicrobial and antifungal activities against different microorganisms. 25,26,27 Furthermore, these fatty acids have high commercial value.…”
mentioning
confidence: 99%
“…44,57 The diterpene, phytol, although not abundant in B. campestris flower oil, may be an important contributor to the activity, since its role in antibacterial activity against oral microorganisms has already been described. 44,51 The EO of the B. campestris flower showed very strong to moderate activity against all the aerobic and anaerobic bacteria tested and could be a natural alternative in the prevention of diseases caused by oral microorganisms. The EO was also evaluated against some yeasts and the results are shown in Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…40,41,46,55,56 The EO of the leaves of Inga laurina collected in rainy season, rich in hexadecanoic acid and phytol, showed significant antibacterial effect against aerobic and anaerobic oral bacteria. 51 Although many classes of metabolites may be present in EOs, the antimicrobial activity is also attributed to the presence of terpenes. 32,35,43,44,51,55 The monoterpenes linalool and α-terpineol have already demonstrated an effect against cariogenic bacteria, including S. mutans, the main etiological agent of dental caries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact mechanism of antibacterial activity of FFA is unknown, but it may be suggested that hydrophobic part is responsible for the activity by interacting with the hydrophobic parts of bacterial cell membrane. Moreover, elongated carbon chain length, presence of double bond and its position also affects antibacterial activity (Furtado et al 2014). Organic compounds having aromatic and phenolic moiety may attribute increased antimicrobial activity to the compound (Patnaik et al 2008).…”
Section: Discussionmentioning
confidence: 99%